Genetic analysis of leukemic transformation of chronic myeloproliferative neoplasms - Abdel-Wahab, Omar (2010)
The genetic events which contribute to transformation of myeloproliferative neoplasms (MPN) to acute myeloid leukemia (AML) are not well characterized. We investigated the role of JAK2, TET2, ASXL1, and IDH1 mutations in leukemic transformation of MPNs through mutational analysis of 63 patients with AML secondary to a preexisting MPN (sAML). We identified frequent TET2 (26.3%), ASXL1 (19.3%), IDH1 (9.5%), and JAK2 (36.8%) mutations in sAML; all possible mutational combinations of these genes were observed. Analysis of 14 patients for which paired samples from MPN and sAML were available demonstrated TET2 mutations were frequently acquired at leukemic transformation (6/14=43%). In contrast, ASXL1 mutations were almost always detected in both the MPN and AML clones from individual patients. A case was also observed where TET2 and ASXL1 mutations were found before the patient acquired a JAK2 mutation or developed clinical evidence of MPN. We conclude that mutations in TET2, ASXL1, and IDH1 are common in sAML derived from a pre-existing MPN. Although TET2/ASXL1 mutations may precede acquisition of JAK2 mutations by the MPN clone, mutations in TET2, but not ASXL1, are commonly acquired at the time of leukemic transformation. These data suggest the mutational order of events in MPN and sAML varies in different patients, and that TET2 and ASXL1 mutations have distinct roles in MPN pathogenesis and leukemic transformation. The presence of sAML with no pre-existing JAK2/TET2/ASXL1/IDH1 mutations indicates the existence of other mutations necessary for leukemic transformation.